ジシン ノ メカニズム カラ ミタ ナンキョク プレート ナイ ノ オウリョクバ - 久保, 篤規; クボ, アツキ; Kubo, Atsuki (1999)
P(論文) 地震のメカニズム解を用いて南極プレート内の特徴的な応力場を抽出した。その結果, 1) Bellingshausen海, 2) Juan-Fernandezマイクロプレート南方沖, 3) Balleny島近傍, 4) Kerguelen島地域, で特徴的な結果が得られた。近傍のリッジ押しのみによって4地域の観測事実を説明するのは困難である。このうち1), 2) での応力場はこれまでリッジ押しで説明されてきたが, データ量の増加とリッジ押しのイメージが明確になったことから, 少なくとも近傍のリッジ押しのみでは応力場は説明できない。3) での地震の起震応力場は, トリプルジャンクション近傍の変形や後氷期地殻変動が震央域を押してやることによって説明可能である。4) では正断層の地震が起こり, ホットスポットなどによる熱応力が重要になる。応力源の特定には定量的モデル化が必要である。大陸内, 大陸縁における応力場は地震が少なく明確な議論は現状では困難である。 Typical directional features of intraplate stresses are extracted from focal mechanism solutions of earthquakes in the Antarctic plate. Typical directions of stresses are obtained in the following regions, 1) Bellingshausen Sea, 2) south of Juan-Fernandez microplate, 3) Balleny Island region and 4) Kerguelen region. P axes in regions 1) and 2) have been interpreted by ridge push force. However these interpretations are based on one focal mechanism for each event and on crude physical concept of ridge push. It is difficult to explain intraplate stress fields in these regions only by the local ridge push force. The stress direction in region 3) can be interpreted by both deformation near triple junction and deformation due to deglaciation. Earthquakes near region 4) appear to be normal fault event. Because normal fault events appear only in the younger ocean floor, the stress field may be affected by thermal features such as hot spots Quantitative modeling and superposition of various stress factors are required to discriminate among stress origins. It is difficult to discuss stress directions in and around Antarctic continent, because number of the earthquakes is not enough. departmental bulletin paper